POPULASI DAN SERANGAN HAMA PUTIH PALSU Cnaphalocrosis medinalis (Guenee) PADA TANAMAN PADI SAWAH DI KECAMATAN DUMOGA TIMUR KABUPATEN BOLAANG MONGONDOW - Anggreini Kilala; Christina L. Salaki; Caroulus S. Rante; James B. Kaligis (COCOS, 2015)
ABSTRACT The research aims to determine the population and attacks Cnaphalocrocis medinalis on paddy rice vegetative phase in District East Dumoga, Bolaang Mongondow. Results are expected to be used as consideration in the preparation of pest control strategies C. medinalis on rice crops in the future. Research using survey method in several centers of rice cultivation in the district of East Dumoga Bolaang Mongondow, then set the 3 villages as research locations or as a sampling. Location criteria based on the presence of the rice research under the age of one week. Sampling using Method Diagonal slices and set up five sub-plot. Observations population conducted by randomly selecting ten clump of rice plants in each sub-plot. C. medinalis larvae contained in the leaf roll is taken, and then collected in a bottle containing 70% alcohol. Samples are labeled according to location and time of uptake, later identified in the Laboratory of Entomology and Pest Plants, Faculty of Agriculture, University of Sam Ratulangi. Observations percentage of attacks carried out by observing each of the 200 plants per sub-plot. Clumps were attacked recorded and calculated to determine the percentage of C. medinalis attack. Sampling was performed four times at intervals of two weeks. The results showed that the population of pests C. medinalis varies at different locations and the highest research found in two locations in the village Dumoga which reached an average of 15.33 tail, then in the village Dumoga Three reached an average of 13.66 tail and in the village of Dumoga Four reached an average of 5.33 birds. Observations highest percentage of attacks was found in the village of Dumoga Two sample sites, reaching 10.54%, then the village of Three Dumoga 9.95% and the lowest is Village Dumoga Four reached 1.53%. Â Keywords : Cnaphalocrosis medinalis, percentage of attacks and populationsÂ